2021
DOI: 10.3390/cryst11070779
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Approaches with Traditional Methods for Predicting the Compressive Strength of Rice Husk Ash Concrete

Abstract: Efforts are being devoted to reducing the harmful effect of the construction industry around the globe, including the use of rice husk ash as a partial replacement of cement. However, no method is available to date to predict the compressive strength (CS) of rice husk ash blended concrete (RHAC). In this study, advanced machine learning techniques (artificial neural network, artificial neuro-fuzzy inference system) were used to predict the CS of RHAC. Based on the published literature, six inputs, i.e., age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Therefore, there exists a natural urge to reuse this waste in construction applications to avoid issues related to their disposal. A general consensus is that optimal advantages are associated with the use of recycled aggregates as compared to the use of natural aggregates in concrete [ 11 , 12 , 13 , 14 ]. Ohemeng et al [ 2 ] concluded that the production of 1 ton of recycled aggregate concrete was 40% cheaper than the cost of natural aggregate concrete having the same volume.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there exists a natural urge to reuse this waste in construction applications to avoid issues related to their disposal. A general consensus is that optimal advantages are associated with the use of recycled aggregates as compared to the use of natural aggregates in concrete [ 11 , 12 , 13 , 14 ]. Ohemeng et al [ 2 ] concluded that the production of 1 ton of recycled aggregate concrete was 40% cheaper than the cost of natural aggregate concrete having the same volume.…”
Section: Introductionmentioning
confidence: 99%
“…Bridging the gaps from atomistic through macroscale behavior of concrete can enable innovation at all necessary scales to advance the development of sustainable concrete. 248 Finally, several machine learning methods have also been used to assess and optimize concrete strength, 249−253 including "better-choice" concrete hybrids that incorporate natural reinforcements or other industrial waste products such as rice husk, 254 sugar cane bagasse ash, 255 green fly ash, 256 zeolite, 257 and silica fume. 258 For more information, we refer the reader to review papers focused on concrete durability.…”
Section: Chemicalmentioning
confidence: 99%
“…Finally, several machine learning methods have also been used to assess and optimize concrete strength, including “better-choice” concrete hybrids that incorporate natural reinforcements or other industrial waste products such as rice husk, sugar cane bagasse ash, green fly ash, zeolite, and silica fume . For more information, we refer the reader to review papers focused on concrete durability …”
Section: Applicationsmentioning
confidence: 99%
“…The traditional mathematical analysis methods for calculating and predicting the compressive strength of the geopolymer paste can lead to complicated calculations, which are time-consuming and provide poor predictability [ 17 ]. The artificial neural network algorithm can theoretically approximate any function.…”
Section: Introductionmentioning
confidence: 99%